2021
DOI: 10.3389/fcimb.2021.637019
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Virulence Characterization of Vibrio vulnificus Isolates From Clinical and Environmental Sources

Abstract: Vibrio vulnificus is a deadly human pathogen for which infections occur via seafood consumption (foodborne) or direct contact with wounds. Virulence is not fully characterized for this organism; however, there is evidence of biochemical and genotypic correlations with virulence potential. In this study, biochemical profiles and virulence genotype, based on 16S rRNA gene (rrn) and virulence correlated gene (vcg) types, were determined for 30 clinical and 39 oyster isolates. Oyster isolates were more biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The importance of distinguishing the C-type when assessing exposure risks in recreational waters is not clear. Both genotypes cause infections in humans and either type can be lethal in mouse models ( 46 ). Comparison of the 16 lethal strains in that study indicates, however, that the average percent mortality was significantly lower for E-type than for C-type ( n = 8 for each type; t test, P = 0.0028).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of distinguishing the C-type when assessing exposure risks in recreational waters is not clear. Both genotypes cause infections in humans and either type can be lethal in mouse models ( 46 ). Comparison of the 16 lethal strains in that study indicates, however, that the average percent mortality was significantly lower for E-type than for C-type ( n = 8 for each type; t test, P = 0.0028).…”
Section: Discussionmentioning
confidence: 99%
“…This bacillus is the deadliest foodborne pathogen with a fatality rate greater than 30 %, however, severity of this condition will depend too on host’s comorbidities [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Two main routes of entry into the bloodstream have been identified in the development of this infection; ingestion of contaminated raw seafood, mainly oysters, and direct bacterial inoculation of skin wounds by direct contact between open wounds and contaminated seawater, or by skin trauma when fishing, handling, or preparation of seafoods [4] , [5] , [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model study of environmental and clinical strains found that isolates with the vcgC allele were more common in clinical strains and were more likely to cause severe infection and death, but isolates with the vcgE allele also were capable of causing lethal infections ( 14 ). Another mouse study utilized strains both from clinical and environmental sources and found no difference in virulence between vcgC and vcgE strains, although isolates obtained from colder temperature seasons were more virulent ( 15 ). Thus, despite many attempts to categorize V. vulnificus , the predictive value of genetic analysis, biochemical assays, and phylogeny to predict pathogenic potential remains unclear.…”
Section: Introductionmentioning
confidence: 99%